2020
DOI: 10.1042/bsr20194070
|View full text |Cite
|
Sign up to set email alerts
|

LINC00221 suppresses the malignancy of children acute lymphoblastic leukemia

Abstract: Correspondence: Man Huang (huangman770@163.com)As the most common malignant disease in childhood, children acute lymphoblastic leukemia (ALL) is a heterogeneous disease caused by the accumulated genetic alterations. Long non-coding RNAs (lncRNAs) are reported as critical regulators in diseases. GEPIA database indicated that long intergenic non-protein coding RNA 221 (LINC00221) was conspicuously down-regulated in acute myeloid leukemia. However, its expression pattern in ALL has not been revealed. This work wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…29 LINC00221 regulates ATP2A2 expression by sponging miR-152-3p, exhibiting anti-proliferation and pro-apoptosis effects in ALL cells. 30 In the study, we found that miR-4500 inhibitors or overexpressed LINC00265 can up-regulate STAT3 expression, whereas miR-4500 mimics or STAT3 shRNAs eliminate the LINC00265-induced malignancy of ALL cells, specifically suppressing ALL cell proliferation and invasion. These results are consistent with the function of STAT3 in breast cancer 31 and head and neck cancer, 32 although they should be further examined in clinical samples.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…29 LINC00221 regulates ATP2A2 expression by sponging miR-152-3p, exhibiting anti-proliferation and pro-apoptosis effects in ALL cells. 30 In the study, we found that miR-4500 inhibitors or overexpressed LINC00265 can up-regulate STAT3 expression, whereas miR-4500 mimics or STAT3 shRNAs eliminate the LINC00265-induced malignancy of ALL cells, specifically suppressing ALL cell proliferation and invasion. These results are consistent with the function of STAT3 in breast cancer 31 and head and neck cancer, 32 although they should be further examined in clinical samples.…”
Section: Discussionmentioning
confidence: 87%
“… 29 LINC00221 regulates ATP2A2 expression by sponging miR-152-3p, exhibiting anti-proliferation and pro-apoptosis effects in ALL cells. 30 …”
Section: Discussionmentioning
confidence: 99%
“…ATP2A2, functioning as an ATP synthase-associated protein, plays a critical role in mitochondrial ion exchange and energy transmission, which significantly influences mitochondrial function[ 25 ]. Furthermore, ATP2A2 has been proven to be instrumental in regulating linc00221-mediated acute lymphoblastic leukemia cell proliferation and apoptosis[ 26 ]. Notably, overexpressed ATP2A2 has also been observed to promote the proliferation of colon cancer and prostate cancer cells[ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, LINC00221 promotes cisplatin resistance in non-small-cell lung cancer, leading to non-effective chemotherapy 28 . Additionally, LINC00221 suppresses the malignancy in acute lymphoblastic leukaemia (ALL) where its overexpression leads to an antiproliferative and pro-apoptotic effect in ALL cells 29 . Within the context of GBM, the literature regarding these four lncRNAs is very scarce.…”
Section: Discussionmentioning
confidence: 99%